Banking innovations and their effect on profitability. - Magallón González, Heber Bernardo; Galeana Figueroa, Evaristo; Prado-Roman, Camilo (Mercados y Negocios, 2022)
This research seeks to answer these questions by analyzing multiple empirical articles carried out at different times, in different countries, and with various innovations. The research is divided into three sections: first, it presents a chronology of the evolution of banks, their main innovations, and events that have modified the banking business model to adapt it to banking today. The second is based on bibliometric tools to present the primary references of the articles that analyze the relationship between innovation and bank profitability and its conceptual structure. Finally, the third section analyzes the concept of branchless banking and its factors. Three findings stand out: 1) according to the empirical literature consulted, it is concluded that innovation does affect profitability, 2) publications have grown in recent years, with China being the most productive country and the United States the most influential, and 3) The concept of branchless banking is a viable alternative to measure innovation in the Mexican banking sector.